FEATURES OF STANDARD PYTHON PROGRAMMING LANGUAGE FUNCTIONS IN SECONDARY SCHOOLS AND TEACHING METHODS - Аknazar uulu, К.; Аzizbek kyzy, Н.; Кoshukulov, М. А. (Вестник Иссык-Кульского университета, 2024)
In the context of the widespread development of modern information technologies, one of the urgent problems is a special approach to teaching programming languages to students of secondary schools, the development of simplified methods of setting tasks in accordance with their age characteristics. The article compares the Python programming language with other programming languages. The advantages of Python programming are defined. This article develops students' knowledge, skills and independent programming skills, develops their interest in programming and helps them find their place in the field of programming in the future, as well as create the best programs for humanity. At present, informatization covers all spheres of human activity, and this phenomenon requires a high information culture from everyone. Therefore, it is necessary to supplement the natural science program of the school with subjects that ensure the development of knowledge, knowledge and skills of students.